2007
DOI: 10.1159/000109944
|View full text |Cite
|
Sign up to set email alerts
|

Neural Connectivity in the Mediobasal Hypothalamus of the Sheep Brain

Abstract: The ventromedial nucleus of the hypothalamus (VMN) and the arcuate nucleus (ARC) are two centres regulating energy balance and food intake, but inter-connectivity of these nuclei is not well defined in non-rodent species. In this study, we performed retrograde tracing and immunohistochemistry in the ovine brain with ewes receiving FluoroGold® (FG) injections into either ARC or VMN for the mapping of retrogradely labelled cells. Strong reciprocal connections were found between the two regions. The distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 158 publications
(121 reference statements)
2
49
0
1
Order By: Relevance
“…in pigs, Kanitz et al 2003, Loijens et al 2002, Piekarzewska et al 1999, Piekarzewska et al 2000, Zanella et al 1996 have demonstrated the involvement of neuropeptides such as CRF and enkephalins in different brain areas including the hypothalamus, brainstem and cortices. While neuroanatomical methods have been used to describe the immunoreactive content of brain areas (in sheep: Tillet 1995; in pigs: Kineman et al 1989, Leshin et al 1996, Niblock et al 2005, Rowniak et al 2008; in large mammals: Tillet & Kitahama, 1998), and neuronaltracing methods have been used to describe the interconnections between some of these brain areas (sheep: Qi et al 2008, Rivalland et al 2006, Tillet et al 1993pigs: Chaillou et al 2009), no dynamic functional information is available about the functional interactions among these different factors. The use of MRI techniques could be an interesting way of gaining a better understanding of the neuronal circuits of animal emotion and other functions.…”
Section: Emotional Reactionmentioning
confidence: 99%
“…in pigs, Kanitz et al 2003, Loijens et al 2002, Piekarzewska et al 1999, Piekarzewska et al 2000, Zanella et al 1996 have demonstrated the involvement of neuropeptides such as CRF and enkephalins in different brain areas including the hypothalamus, brainstem and cortices. While neuroanatomical methods have been used to describe the immunoreactive content of brain areas (in sheep: Tillet 1995; in pigs: Kineman et al 1989, Leshin et al 1996, Niblock et al 2005, Rowniak et al 2008; in large mammals: Tillet & Kitahama, 1998), and neuronaltracing methods have been used to describe the interconnections between some of these brain areas (sheep: Qi et al 2008, Rivalland et al 2006, Tillet et al 1993pigs: Chaillou et al 2009), no dynamic functional information is available about the functional interactions among these different factors. The use of MRI techniques could be an interesting way of gaining a better understanding of the neuronal circuits of animal emotion and other functions.…”
Section: Emotional Reactionmentioning
confidence: 99%
“…The receptor for orexin (OX1R) was localized to the ARC, median eminence, lateral hypothalamic nuclei and ventral portion of the preoptic area (Zhang et al, 2005). Interestingly, ORX neurons originating in the LHA provide input to both the ARC and VMN (Qi et al, 2008). Combined, these studies link ORX to regions of the hypothalamus related to feed intake, endocrine, metabolic and reproductive regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In colchicine-treated sheep, NPY neurons were found distributed between two populations of cells within the ARC, median eminence, pituitary stalk, the dorsomedian and dorsocaudal nuclei, and in the periventricular nucleus (PeVN; Polkowska et al, 2006a), but were absent in the magnocellular neurons of the paraventricular and supraoptic nuclei (Chaillou et al, 2002;Chaillou and Tillet, 2005). There is also a rich interconnection between the ARC and VMN in sheep (Qi et al, 2008). In addition, numerous studies have demonstrated expression of NPY mRNA in the ARC Adam et al, 2002;Pillon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations